Career Concerns, Risk-Taking, and Upward Mobility in the Financial Services Industry: Evidence from Top Ranked Financial Advisers - Jun Honda (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2020)
We investigate career concerns of financial advisers with a focus on their risk-taking and upward mobility. We use matched employer-employee data for the universe of financial advisers with one well-known national ranking for top financial advisers. We find that at early career stages before being ranked, top advisers (i) are twice as likely to acquire a certain license to serve as investment adviser, (ii) encounter customer disputes way more frequently (up to seven times), and (iii) switch to a firm of 80% larger size as measured by total assets, than average advisers. We also find that top advisers manage high risks through labour-market penalty reduction associated with disciplinary actions. Lastly, using variations in rm policy for recruitment across firms, we provide evidence that reducing frictions in job mobility yields sorting dynamics that employers recruit high productive workers intensively within a short time window.
Keywords: G24; J44; L22; 330; Career Concerns; Financial Advisers; Job Mobility; Risk-Taking; Sorting